Thinking Europe otherwise: lessons from the Caribbean - Boatcă, Manuela (2021)
Abstract: The article makes a case for Europe as a creolized space, or Europe Otherwise. It argues that, in order to account for both the transregional entanglements and the internal hierarchies that European colonialism and imperialism have produced since at least the sixteenth century, we need to unlearn received notions of Europe as an unmarked category; and that theoretical and empirical lessons from the Caribbean are central to relearning Europe differently. To conceive of Europe as a creolized space thus means to draw attention to the decisive shifts that its colonial possessions operate in both its historical legacies and its present borders when consistently taken into account. Such reconceptualization entails a simultaneous creolization of theory so as to reinscribe into sociological thought the experiences of peoples and regions racialized as non-European, non-Western, and non-White alongside the multiple entanglements between Europe and its colonies. Drawing on Caribbean perspectives on creolization, I first discuss how creolizing Europe contributes to countering the definition power of ahistorical and unmarked categories. Subsequently, I propose to rethink Europe as a political, cultural, economic, and discursive formation from its current colonial borders in South America and the Caribbean Sea. Finally, I argue that focusing on Europe’s colonial possessions in the Caribbean today and their corresponding geographical referent, Caribbean Europe, is one way to effectively creolize established understandings of Europe’s colonial history as a thing of the past, of a white Western European identity as the norm, and of the European Union as confined to continental Europe. Recent crises in the Caribbean – from the 2017 hurricanes to Brexit – are used as a magnifying glass in order to make Europe’s ongoing colonial entanglements theoretically and politically visible